Karakteristik ibu balita dalam pemantauan pertumbuhan dan perkembangan balita - Susilawati Susilawati (Jurnal Kebidanan, 2020)
In monitoring the growth and development of children, the role of parents is very important. Early detection by parents can identify 1 – 6% of children who have developmental disorders. Parents who did not monitor their child's growth and development were 34.3%. It causes many children whose growth and development have not been observed. The incidence rate of developmental disorders in children is known to be around 33.5%. The purpose of this study was to determine the characteristics of mothers of children under five in monitoring the growth and development of infants in Pusksmas Babakan Sari Bandung City. Descriptive research design with cross-sectional approach. This study used Accidental Sampling, as many as 53 mothers of children under five—data analysis using univariate analysis. The results showed that the characteristics of mothers of children under five were mostly at the age of 20 - 35 as many as 30 mothers (56.6%), high school education as 29 mothers (54.8%), family income with a high category of 27 mothers (50.9%), having children ≥ 2 as many as 37 mothers (69.8%), and not working as many as 44 mothers (83%).